Análisis de la efectividad y oportunidad de la atención médica que otorga el Seguro Social Campesino a la Población Rural del Cantón Paltas, Provincia de Loja, Año 2013 - Herrera Saraguro, Alvaro Enrique (2016)
It is well known that the shortage of medicines at the clinics and treatment level of transfers to social security are problematic due to the current passing through the rural social security beneficiaries derived from the medical care given. It was deemed appropriate to analyze the effectiveness and timeliness as variables of quality care from the point of view of the beneficiaries. Effectiveness as Understood by (Donabedian, 1991) "the level at which health care is delivered correctly, looking to improvements in patient health by improving the impact of disease on a defined population" under features; care consultation, medicalization, patient appointment and conduct of preventive campaigns. As for the effectiveness of medical care to patients of peasant insurance canton avocados , it was concluded that if properly applied level clinics Canton , since it was known that 63,6% said the doctor clarifies " always " all doubts of the condition of the patient; 80,3% mentioned that supplies the appropriate drugs for improvement , as long as they exist in the clinic pharmacy; 81,1% said the doctor if you set controls based on severity and condition presented by the patient and 70,9% say that if they carry out the execution of preventive campaigns at the organizational level . Regarding the opportunity to care for patients in rural social security Avocado , is conceived as " the possibility that the patient get the assistance they need without exhibiting setbacks that endanger their health " (PEREIRA, Accreditation in Health, 2010, p. 12). Circumstances that give rise to dissatisfaction among patients, was analyzed including: favorable situations the patient to visit the clinic; staff available, speed of action, drug available, availability of stretchers and wheelchairs and warmth of the staff. Also for this variable, the treatment of transfers from its concession and subsequent allocation to external health service providers. With regard to the parameters of the opportunity of medical care, 78,2% of patients state that predominates year Lack of medicines in clinics and 82.2 % argue that in the clinic they attended, no wheelchairs and stretchers to mobilize the patient to the clinic internally. Regarding transfers needed assigned to be transferred, the 61,34% of patients claim that prior medical evaluation where the discomfort originates from the patient seeks medical appointment allocation through the call center was made Social Security, once from the dispensaries were granted the transfer, which the 34,5% of patients transferred attest that since I have been assigned the appointment, your wait is over 30 days. Finally with the above background, it can be concluded that not work effectively in the field of delivery of all medications prescribed to patients and in terms of opportunity indeed found to dominate those problems related to the availability of drugs in dispensaries and patient discomfort by waiting for the appointment when they are transferred. As the perception of patients about medical care in clinics reflected by the satisfaction level 53,9% asserts that attention is good, while 44,2% say is regular and only 1,9% ensures quality is poor.